The effect of listening to music on the physiological responses of children with special needs - Zhou, Zhenyu; Chang, Zhenhua (Música Hodie, 2023)
The aim of the work is to study the ability of children with a mild ID and children with a normal level of development to perceive and differentiate emotions received while listening to music. Group 1 included 100 schoolchildren with a mild ID, group 2 - other 100 schoolchildren with a normal level of development. There were no significant changes in the intellectual development of children with a mild ID due to long-term listening to music, but this method is suitable for correcting the psycho-emotional state of children from group 1. Productivity was higher with musical accompaniment.